Deficient leptin receptor signaling in T cells of human SLE - Liu, Ting; Zheng, Ming; Jia, Li; Wang, Mingyuan; Tang, Longhai; Wen, Zhenke; Zhang, Miaojia; Yuan, Fenghong (Frontiers in Immunology, 2023)
Background: Systemic lupus erythematosus (SLE) is a prototypic autoimmune disease mainly mediated by IgG autoantibody. While follicular helper T (Tfh) cells are crucial for supporting IgG autoantibody generation in human SLE, underlying mechanisms for Tfh cell mal-differentiation remain unclear. Methods: In total, 129 SLE patients and 37 healthy donors were recruited for this study. Circulating leptin was determined by ELISA from patients with SLE and healthy individuals. CD4 T cells isolated from SLE patients and healthy donors were activated with anti-CD3/CD28 beads under cytokine-unbiased conditions in the presence or absence of recombinant leptin protein, followed by detection for Tfh cell differentiation by quantifying intracellular transcription factor Bcl-6 and cytokine IL-21. AMPK activation was assessed by analyzing phosphor-AMPK using phosflow cytometry and immunoblots. Leptin receptor expression was determined using flow cytometry and its overexpression was achieved by transfection with an expression vector. Humanized SLE chimeras were induced by injecting patients’ immune cells into immune-deficient NSG mice and used for translational studies. Results: Circulating leptin was elevated in patients with SLE, inversely associated with disease activity. In healthy individuals, leptin efficiently inhibited Tfh cell differentiation through inducing AMPK activation. Meanwhile, leptin receptor deficiency was a feature of CD4 T cells in SLE patients, impairing the inhibitory effect of leptin on the differentiation of Tfh cells. As a result, we observed the coexistence of high circulating leptin and increased Tfh cell frequencies in SLE patients. Accordingly, overexpression of leptin receptor in SLE CD4 T cells abrogated Tfh cell mal-differentiation and IgG anti-dsDNA generation in humanized lupus chimeras. Conclusion: Leptin receptor deficiency blocks the inhibitory effect of leptin on SLE Tfh cell differentiation, serving as a promising therapeutic target for lupus management.